Structure and diversity of the trees of Parque Hundido, Monterrey, Nuevo León - Alanís-Rodríguez, Eduardo; Cuéllar-Rodríguez , Gerardo; Jiménez-Pérez, Javier; Mora-Olivo, Arturo; Ita-Garay, Ada Marcela (Ecosistemas y Recursos Agropecuarios, 2023)
The evaluation of tree structure and diversity has been of vital importance for the planning and management of urban forests. Unfor- tunately, there are currently numerous wooded areas in cities, where the current status of the species present is unknown. The objective of this study was to evaluate the structure and diversity of the trees in Parque Hundido, which is in the metropolitan area of Monterrey, Nuevo León. In September 2021, all the trees and shrubs were registered and their total height and crown length, normal diameter, and crown diameter were measured. As a result, 26 species were identified, of which 11 were native and 15 intro- duced. The species that presented the highest values of abundance, crown area and frequency were Fraxinus uhdei, Fraxinus americana and Ehretia anacua. The graphs of diameter and height classes indicate that there is a greater proportion of trees with intermediate diameters and heights, which indicates an adult plant community. The richness and diversity values were intermediate, like other urban green areas in northeastern Mexico. It is concluded that native tree plants are more important than exotic ones in Parque Hundido.